METHODOLOGY OF PERFORMANCE OF OBJECTIVES AND TASKS IN FORMING A CULTURE OF LIFE SAFETY - Rasuleva M.A; Muminov O (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Revealing the qualities and properties of FOLSC objects, as well as the methods and tools that affect these qualities and characteristics, the formation of a culture of public safety is one of the most effective tools for managing the worldview of a recognized person and society. The radical solution to this problem is to educate themselves in a safe way so that they can ensure their own safety at a higher level than that of others, at a level of advanced spirituality, skills, and ability.